Los Sorítidos del Cretácico de la Cordillera Ibérica (España) - Calonge Garcia, Amelia (Coloquios de Paleontología, 1996)
This paper deals with the species of the family Soritidaeidentified until now in the Middle Cretaceous of the Iberian Ranges and it is proposed its biostratigraphical distribution. Theses species are Pseudorhipidionina casertana, Pseudorhapydionina dubia, P lauí-inensis and Peneroplis parvas which verlical distribution with Alveolinids species allow us to obtain accurate results abouí the age of the beds in which they are present. So, Peneroplis parvas with Ovalveolina maccagnoae and Pseudedomia vial/ii belonging to Ihe Lower Cenomanian. Qn the other hand, Pseudorhipidionina caserta Dpt<t (Jeologia. Universidad de Alcalá. 28871 Alcalá de Henares (Madrid). * <o/o quhss de Paleontología, ni 48: 25-45. Servicio de Publicaciones U.C.NI. Madrid, 1996 26 Amelia Calonge Garció na and Pseudorhapydionina dubia as well as Alveolinids: Pracalveolina cretacea, P. debilis and Simplalveolina simple> dated the top of the Middle Cenomanian. Finally, l-'seudorhapydionina laurinensis with Pseudohipidionina casertana and Pseudorhapyáionina dubia, as well as Alveolinids: Pracalveolina tenuis; P. caseríana, Ovalveolina ovum and Simpialveolina simplex suggested Ihe Upper Cenomanian.